Childhood theory of mind does not predict psychotic experiences and social functioning in a general population sample of adolescents. - Laura A Steenhuis; Gerdina H M Pijnenborg; Jim van Os; André Aleman; Maaike H Nauta; Agna A Bartels-Velthuis (PLoS ONE, 2019)
AIMS:Theory of Mind (ToM) is often impaired in early and chronic phases of psychosis and it is often suggested that poor ToM is a trait vulnerability for psychosis. The aim of this study was to examine in an adolescent sample whether childhood ToM abilities can predict psychotic experiences over a period of six years and whether this is mediated by social functioning. To examine whether ToM is a specific predictor for psychosis, symptoms of depression and anxiety were also examined. MATERIALS AND METHODS:A baseline case-control sample (T0: age 7-8 years) with and without auditory vocal hallucinations (AVH) in the general population was assessed after five years (T1: age 12-13 years) on ToM ability (ToM Storybook Frank), and after eleven years (T2: age 18-19 years) on psychotic experiences (Community Assessment of Psychic Experiences; CAPE), depressive and anxiety symptoms (Depression Anxiety and Stress Scale; DASS-21), and social functioning (Groningen Questionnaire on Social Behaviour; GSVG-45). Analyses were conducted on a subsample of 157 adolescents aged 18-19 years (T2) who had data available on ToM ability at T1. RESULTS:ToM at T1 was not predictive of psychotic experiences after six years (from age 12-13 to age 18-19) and social functioning was also not a mediator. ToM was not associated with psychopathology in general (depressive and anxiety symptoms) over six years (from age 12-13 to age 18-19). CONCLUSIONS:The current study found no evidence for a longitudinal association between ToM ability and psychotic experiences, social functioning, and symptoms of depression and anxiety, in adolescence.